Muscle wasting and aging: Experimental models, fatty infiltrations, and prevention. (August 2016) - Brioche, Thomas; Pagano, Allan F.; Py, Guillaume; Chopard, Angèle
Abstract: Identification of cost-effective interventions to maintain muscle mass, muscle strength, and physical performance during muscle wasting and aging is an important public health challenge. It requires understanding of the cellular and molecular mechanisms involved. Muscle-deconditioning processes have been deciphered by means of several experimental models, bringing together the opportunities to devise comprehensive analysis of muscle wasting. Studies have increasingly recognized the importance of fatty infiltrations or intermuscular adipose tissue for the age-mediated loss of skeletal-muscle function and emphasized that this new important factor is closely linked to inactivity. The present review aims to address three main points. We first mainly focus on available experimental models involving cell, animal, or human experiments on muscle wasting. We next point out the role of intermuscular adipose tissue in muscle wasting and aging and try to highlight new findings concerning aging and muscle-resident mesenchymal stem cells called fibro/adipogenic progenitors by linking some cellular players implicated in both FAP fate modulation and advancing age. In the last part, we review the main data on the efficiency and molecular and cellular mechanisms by which exercise, replacement hormone therapies, and β-hydroxy-β-methylbutyrate prevent muscle wasting and sarcopenia. Finally, we will discuss a potential therapeutic target of sarcopenia: glucose 6-phosphate dehydrogenase.